KEANEKARAGAMAN KOMUNITAS MAKROBENTHOS PADA EKOSISTEM MANGROVE DI DESA BANYUURIP KECAMATAN UJUNG PANGKAH KABUPATEN GRESIK - Madyowati, Sri Oetami; Kusyairi, Achmad (JFMR (Journal of Fisheries and Marine Research), 2020)
Mangrove Ecosystem in the Banyuurip Village Ujung Pangkah District Gresik Regency is a coastal area that has a fairly extensive mangrove forest and human activities are also increasing, it will directly affect the existence of biota in the mangrove ecosystem, one of the affected biota are macrobentos. The purpose of this study is to determine the community structure (species composition, average abundance, and relative abundance) and Ecological Index (Diversity Index and Dominance Index) macrobenthos. Determination of the station based on the condition of mangrove forests, substrate and surrounding activities, consisting of 3 stations namely station 1 in residential areas, station 2 at the residents' water gate, station 3 at the river mouth near the ocean. The results obtained were 15 species of macrobenthos diversity, divided into 10 types of Gastropoda class, 4 types of Malacostraca class and 1 type of Polychaeta class. Makrobentos abundance between 114 ind / m2 to 159 ind / m2. Diversity Index between 1.6605 and 2.5737. Dominance Index between 0.0803 to 0.2669. The structure of the macrobenthos community is stable with a diversity of species and the distribution of the number of individuals of each species is evenly distributed, the community is uniform and there are no species that dominate so that the environmental conditions in the Mangrove Ecosystem in Banyuurip Village District Ujung Pangkah Gresik Regency is said to be still good.Â